Objective Evidence of Pulsus Alternans by Echocardiography in Acute Severe Heart Failure - Fatema, Nilufar; Mandal, Rayhan Masum; Arzu, Jahanara; Habib, SM Ahsan; Ahmad, Khurshed; Rahman, Fazlur; Banerjee, Sajal Krisna; Ahmed, Chaudhury Meshkat; Hoque, Md Harisul (University Heart Journal, 2020)
Acute coronary syndrome may leads to heart failure. Severity of heart failure is identified by NYHA classification clinically. Color Doppler echocardiography is the key investigation to identify the acute systolic heart failure. For the quantification of systolic heart failure diagnosis, Ejection fraction (EF) can be measured by Simpson method. EF > 30% is defined as severe systolic heart failure. Pulsus alternans is found in severe heart failure patients. Pulsus alternans is a poor prognostic sign of severe heart failure patients in acute MI setting. This cross sectional observation study was aimed to identify the objective evidence of Pulsus alternance noninvasively by Echocardiography. Color Doppler echocardiography was done 100 acute coronary syndrome with heart failure NYHA III and IV patients in department of Cardiology, BSMMU, from July 2018 to June 2019. Age 18 to 70 yrs, male is 79 and female is 21. Pulsus alternans was found in 32 patients, 39 had low volume and 29 had normal volume pulse. 50% patients had ST depression and T inversion and diagnosed as case of Unstable Agina or Non STEMI, 44 had STEMI and 7 had developed new onset of LBBB. 87 Patients who have EF < 30 % was marked as Severe LV systolic dysfunction. Among them, 3 had mild, 14 had moderate and rest 70 had severe Mitral regurgitation. 38 (43.67%) patients had Doppler alternans in severe LV systolic dysfunction group. P value for Doppler alternans is 0.039 which is significant. Doppler alternans by Echocardiography in Severe LV systolic dysfunction patients showed 49% sensitivity and 78% specificity. 38 patients had Severe RV systolic dysfunction by M- mode echo measurement of TAPSE<10 mm. 22 (57.89%) had Doppler alternans across Tricuspid valve in case of severe RV systolic dysfunction. Sensitivity of Doppler alternans by Doppler Echocardiography in TV severe RV systolic dysfunction is 51% and specificity for it is 82%. University Heart Journal Vol. 16, No. 2, Jul 2020; 92-98